Evolving the Scope of 5, 5'‐Azobistetrazoles in the Search for High Performing Green Energetic Materials. Issue 30 (16th August 2021) - Benz, Maximilian; Gruhne, Michael S.; Klapötke, Thomas M.; Krüger, Nina; Lenz, Tobias; Lommel, Marcus; Stierstorfer, Jörg
Abstract: The azotetrazole moiety represents a great platform for energetic materials, it offers a planar and nitrogen‐rich backbone, combined with a high heat of formation, which easily can be functionalized and tuned. Herein, we start from sodium 5‐aminotetrazolate and obtain two isomers by substitution reaction with 2‐chloroethanol. Azidoethyl and nitratoethyl substituted azo‐ tetrazoles were finally synthesized by oxidative azo coupling of the respective N ‐ethyl functionalized 5‐aminotetrazole precursors using tert ‐butyl hypochlorite as reagent. All compounds were analyzed through multicore NMR and IR spectroscopy as well as mass spectrometry. All solid compounds were further investigated using low‐temperature X‐ray crystallography. The purity was verified by CHNO elemental analysis and the decomposition temperature (DTA) and sensitivities toward impact, friction and electrostatic discharged were determined. Based on the CBS‐4M calculation results, the energetic properties were calculated using the EXPLO5 code. Abstract : Tert ‐butyl hypochlorite is a powerful, cheap and handy reagent for performing oxidative azo coupling of aminotetrazoles. By the formation of differently substituted azotetrazoles, new energetic molecules were created through an elegant synthetic route.